Nacnac-Cobalt-Mediated P4Transformations - Spitzer, Fabian; Grassl, Christian; Balazs, Gabor; Maedl, Eric; Keilwerth, Martin; Zolnhofer, Eva; Meyer, Karsten; Scheer, Manfred (Chemistry - A European Journal, 2017)
A comparison of P4activations mediated by low-valent β-diketiminato (L) cobalt complexes is presented. The formal Co0source [K2(L3Co)2(μ2:η1,η1-N2)] (1) reacts with P4to form a mixture of the monoanionic complexes [K(thf)6][(L3Co)2(μ2:η4,η4-P4)] (2) and [K(thf)6][(L3Co)2(μ2:η3,η3-P3)] (3). The analogue CoIprecursor [L3Co(tol)] (4 a), however, selectively yields the corresponding neutral derivative [(L3Co)2(μ2:η4,η4-P4)] (5 a). Compound 5 a undergoes thermal P atom loss to form the unprecedented complex [(L3Co)2(μ2:η3,η3-P3)] (6). The products 2 and 3 can be obtained selectively by an one-electron reduction of their neutral precursors 5 a and 6, respectively. The electrochemical behaviour of 2, 3, 5 a, and 6 is monitored by cyclic voltammetry and their magnetism is examined by SQUID measurements and the Evans method. The initial CoI-mediated P4activation is not influenced by applying the structurally different ligands L1and L2, which is proven by the formation of the isostructural products [(LCo)2(μ2:η4,η4-P4)] [L=L3(5 a), L1(5 b), L2(5 c)].
CRIS-Team Scopus Importer:2020-09-14
Keywords: cyclic voltammetry; paramagnetic NMR; small molecule activation; white phosphorus; β-diketiminates